[tex]\bf \textit{equation of a circle}\\\\ (x- h)^2+(y- k)^2= r^2 \qquad center~~(\stackrel{-\frac{1}{50}}{ h},\stackrel{\frac{1}{3}}{ k})\qquad \qquad radius=\stackrel{\frac{1}{2}}{ r} \\\\\\ \left[ x-\left( -\frac{1}{50} \right) \right]^2+\left[ y-\frac{1}{3} \right]^2=\left( \frac{1}{2} \right)^2\implies \left( x+\frac{1}{50} \right)^2+\left( y-\frac{1}{3} \right)^2=\frac{1^2}{2^2} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ ~\hfill \left( x+\frac{1}{50} \right)^2+\left( y-\frac{1}{3} \right)^2=\frac{1}{4}~\hfill[/tex]